2010
DOI: 10.1007/s00125-010-1838-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different doses of vitamin D3 on markers of vascular health in patients with type 2 diabetes: a randomised controlled trial

Abstract: Aims/hypothesis Low 25-hydroxyvitamin D levels predict future cardiovascular events and are common in patients with type 2 diabetes. We compared the effect of 100,000 and 200,000 IU doses of vitamin D 3 on endothelial function, blood pressure and markers of glycaemic control in patients with type 2 diabetes. Methods This was a randomised, parallel group, placebocontrolled trial. Patients with type 2 diabetes and baseline 25-hydroxyvitamin D levels <100 nmol/l were enrolled from community and hospital-based dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
210
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(218 citation statements)
references
References 35 publications
6
210
1
1
Order By: Relevance
“…Funnel plots examining fasting glucose (the most commonly measured outcome) for the normal fasting glucose and abnormal glucose tolerance subgroups revealed no asymmetry to suggest publication bias (see also Supporting Information, Figures S1 and S2). We used individual patient level data from two studies [3,22] to confirm that the standard deviation of change in fasting glucose and HbA 1c imputed from the start and finish standard deviation was similar to or greater than the real standard deviation for each treatment group, thus confirming that this approach did not overstate the precision of effect estimates.…”
Section: Study Quality and Biasmentioning
confidence: 98%
“…Funnel plots examining fasting glucose (the most commonly measured outcome) for the normal fasting glucose and abnormal glucose tolerance subgroups revealed no asymmetry to suggest publication bias (see also Supporting Information, Figures S1 and S2). We used individual patient level data from two studies [3,22] to confirm that the standard deviation of change in fasting glucose and HbA 1c imputed from the start and finish standard deviation was similar to or greater than the real standard deviation for each treatment group, thus confirming that this approach did not overstate the precision of effect estimates.…”
Section: Study Quality and Biasmentioning
confidence: 98%
“…The quality assessment of the studies resulted in 14 out of 23 studies having a good quality (Appendix 1, see section on Appendix given at the end of this article) (12,19,20,21,22,23,24,25,26,27,28,29,30,31). The main characteristics and main outcomes of the included studies are given in Table 1.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…A meta-analysis of four prospective and fourteen cross-sectional studies found a pooled OR of 0·73 (95 % CI 0·63, 0·84) for hypertension in participants in the highest 25(OH)D category compared with those in the lowest category (73) . A number of RCT have measured changes in BP (primarily clinic BP) in response to vitamin D supplementation and shown mixed results (74)(75)(76)(77)(78)(79)(80) .…”
Section: Blood Pressurementioning
confidence: 99%
“…A couple of cross-sectional studies in healthy adults show lower serum levels of 25(OH)D to be associated with endothelial dysfunction (91,92) . A few trials show an improvement in flow-mediated dilation with vitamin D supplementation (93)(94)(95) , but most show no effect (79,(96)(97)(98) ( Table 2).…”
Section: Endothelial Functionmentioning
confidence: 99%